Realization of pratuokng (bamboo tube zither) repertoire among the Bidayuh of Annah Rais through frequency modulation synthesis sound modeling - Musib, Ahmad Faudzi (Universiti Putra Malaysia Press, 2019)
Gongs are heard during Gawai celebration on first and second of June every year as an indication of appreciation for the harvest obtained. Gongs are a symbol of prosperity for the Bidayuh (Horsbourgh, 1858). Gong players gather and perform and are frequently joined by the traditional Bidayuh dance at an open space, 'awah' of the longhouse known as 'Kupuo'. There are three levels of tone attribute derivative from the gongs, namely 'canang', 'satu' and 'tawak'. In the community of Annah Rais, Padawan, Sarawak, there are tube zithers known as pratuokng, which contain a similar tone structure as the Bidayuh gong set and offer comparative collections. Seen from the point of view of sound preservation, the Audiovisual Research Collection for Performing Arts (ARCPA) located at the Music Department of Faculty of Human Ecology, UPM is stepping forward in developing elusive learning for a scholarly group to get to far-reaching database collections. In this respect, an exploratory examination concerning pratuokng collection is directed by means of sound simulation via Frequency-Modulation Synthesis (FM Synthesis), draws nearer as a model. The 'Audio Modulation' method, especially by means of frequency modulation, empowers summing sine wave to be a structure at different amplitudes. Subsequently, creating a non-consonant partials of frequencies sidebands will build up a metallic timbre, empowering the acknowledgment of the pratuokng music back in the traditional Bidayuh gong ensemble.